The use of artificial intelligence in the hospitality industry: Understanding customer service interactions with smart speakers - Ruiz-Equihua, D.; Romero, J.; Casaló, L. V.; Loureiro, S. M. C. (Proceedings of AIRSI 2022: Technologies 4.0 in tourism, service and marketing, 2022)
Artificial intelligence machines exhibit human aspects such as human voice, human physical appearance, or a degree of human intelligence, allowing companies to use it in services such the health care or hospitality ones (Huang and Rust, 2018). In this regard, the advent of artificial intelligence machines is changing customer frontline experiences in services such as the hospitality ones (e.g., Yoganathan et al., 2021). For example, customers can order food to a robot in a restaurant, ask for a drink to a voice assistant in a hotel, or converse with a chatbot in a company’s website. Among all these initiatives, 78% of hotel companies consider that voice assistants devices would be in mass adoption for 2025 (Oracle, 2018). Specifically, voice assistants are “voice-controlled devices designed to provide personal assistance for users’ daily activities” (Whang and Im, 2021, p.581), and the most known voice-assistant are the ones included in smart speakers such as Amazon Echo and Google Home. Smart speakers are devices provided with artificial intelligence which can perform several tasks such as reporting the weather forecast, switching off the light, or playing music (Romero et al., 2021)g music (Romero et al., 2021). These devices, employing artificial intelligence, are able to “converse” with people (Belanche et al., 2020), arising perceptions of social interactions resulting in favorable customer responses (van Doorn et al., 2017). Thus, this research aims to enhance the understanding of how and why customer-smart speaker interactions generates favorable customer responses in the hospitality industry. To do so, this research focuses on the influence of smart speakers in customers frontline experiences on the hospitality industry, specifically in hotels. Thus, we propose the following research questions: RQ1: which positive aspects customers highlight in online reviews regarding their positive experiences using a smart speaker in hotels? RQ2: which is the mechanism through which positive customer responses arise from the interaction with smart speakers in hotels? RQ3: which are the actual behaviors from customers that interacts with smart speakers in hotels? To answer these questions, this research conducts three studies that are detailed in the subsequent sections.